2015
DOI: 10.1007/s13139-015-0378-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of F-18 FDG PET/CT in Papillary Thyroid Cancer with Negative Radioiodine Scan and Elevated Thyroglobulin Level or Positive Anti-thyroglobulin Antibody

Abstract: F-18 FDG PET/CT, although less sensitive, showed high specificity, PPV, NPV, and accuracy and therefore can be useful for the patients with negative diagnostic radioiodine scan and elevated serum Tg or positive TgAb. In addition, FDG PET/CT under ETS does not seem to have an additive role in detecting recurrence in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
2
17
1
1
Order By: Relevance
“…However, a negative 131 I scintigraphy result in a sTg-positive patient is a diagnostic and therapeutic challenge 11 . Using PET/CT in this group of patients is widely accepted, however, low sensitivity observed in patients with slightly increased sTg levels reflects that higher Tg level may be required to achieve a better FDG-PET accuracy 14 17 , 25 , 26 . Recent studies have suggested 99m Tc-3PRGD2 as a promising modality for guiding diagnosis and treatment of metastatic DTC lesions 22 , 27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a negative 131 I scintigraphy result in a sTg-positive patient is a diagnostic and therapeutic challenge 11 . Using PET/CT in this group of patients is widely accepted, however, low sensitivity observed in patients with slightly increased sTg levels reflects that higher Tg level may be required to achieve a better FDG-PET accuracy 14 17 , 25 , 26 . Recent studies have suggested 99m Tc-3PRGD2 as a promising modality for guiding diagnosis and treatment of metastatic DTC lesions 22 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients were regarded as recurrence negative if either, (1) histopathological examination by either biopsy or reoperation excluded recurrence, or (2) other imaging modalities did not display recurrent disease and sTg levels spontaneously dropped. Using this definition of recurrence, we evaluated the diagnostic value of 99m Tc-3PRGD2 SPECT/CT to disclose recurrent disease in our patients 2 , 10 14 , 37 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorine-18-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/X-ray computed tomography (PET/CT) is an established imaging modality in cases with TENIS syndrome [ 18 20 ]. However, the low probability of obtaining a positive FDG PET result in TENIS patients with sTg levels lower than 30 ng/mL may hamper its clinical use [ 19 , 20 ]. Previous studies have focused on the ability of 99m Tc-PEG4-E [PEG4-c (RGDfK)]2 ( 99m Tc-3PRGD2) SPECT/CT to specifically image metastatic lymph nodes in DTC patients [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%